Unravelling Lessonia trabeculata management in coastal areas of the Atacama region of northern Chile through a DPSIR approach: Insights for sustainable plans. (November 2021) - Campos, Leonardo; Berrios, Fernando; Oses, Rómulo; González, Jorge E.; Bonnail, Estefanía
Abstract: Subtidal Lessonia trabeculata is one of the primary kelp resources of northern Chile. It is an ecosystem engineer that provides habitat, shelter, and food for invertebrates and fish. This fishery has been developed by a collection of stranded algae carried out by legally registered fishers and illegal collectors in open-access areas and management and exploitation areas for benthic resources. Due to the current high demand on the international market, the collection of dead plants is supplemented by direct extraction. In response, a management plan has been implemented to regulate extraction efforts and institute annual quotas. The dynamics of the L. trabeculata fishery in the Atacama region over 20 years were evaluated using the conceptual framework of the driver-pressure-state-impact-response (DPSIR) approach. The fishing dynamics are strongly conditioned by price fluctuations, promoting the growth of fishing efforts (pressure) in response to economic indicators (driving forces). This often leads to a high volume of extractions of resources (impact) reflected in the increase in extractors and landings in spite of the establishment of quotas (responses), that generate intense pressure on local populations of algae and other commercially important fish and invertebrates (state). A lack of knowledge was detected regarding population aspects and its associated communities. Consequently, this kelp has been mismanaged without a specific focus on this species. Finally, the indicators included in the present DPSIR analysis enable a global understanding of the L. trabeculata fishery, and it should be considered as a basis for future studies and the implementation of resource management strategies.